Transmission interference microscopy of anterior human eye - Samer Alhaddad; Wajdene Ghouali; Christophe Baudouin; Albert Claude Boccara; Viacheslav Mazlin (Nature Communications)
Abstract Cellular imaging of the human anterior eye is critical for understanding complex ophthalmic diseases, yet current techniques are constrained by a limited field of view or insufficient contrast. Here, we demonstrate that Ernst Abbe’s foundational principles on the interference nature of transmission microscopy can be applied in vivo to the human eye to overcome these limitations. The transmission geometry in the eye is achieved by projecting illumination onto the posterior eye (sclera) and using the back-reflected light as a secondary illumination source for anterior eye structures. Specifically, we show that the tightly localized illumination spot at the sclera functions analogously to a closed condenser aperture in conventional microscopy, significantly enhancing interference contrast. This enables clear visualization of cells and nerves across all corneal layers within an extended 2 mm field of view. Notably, the crystalline lens epithelial cells, fibers, and sutures are also distinctly resolved. In patients, Fuch’s endothelial dystrophy - a major ophthalmic disease affecting 300 million people - is highlighted under a transmission contrast, providing complementary information to traditional reflection contrast. Constructed using consumer-grade cameras, the instrument offers a path toward broad adoption for pre-screening and surgical follow-up, as well as for diagnosing corneal infections in low-resource settings, where anterior eye diseases are most prevalent.